2005
DOI: 10.1111/j.1365-2133.2005.06554.x
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells successfully improve skin-substitute wound healing

Abstract: These data suggest that hMSCs together with bFGF in a skin defect model accelerate cutaneous wound healing as the hMSCs transdifferentiate into the epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(168 citation statements)
references
References 22 publications
4
159
0
5
Order By: Relevance
“…Thus, the secretion of IL-6 by the constitutive activation of the p38 MAPK pathway in MSCs under wound healing; however, discrepancies existed in exploring the underlying mechanisms. MSCs were found serum depletion or hypoxic conditions may act as one of the endogenous responses to various stresses, endowing to mediate the effects by differentiating into skin (25), vessel (12), or neural cells (16), by secreting paracrine tissues or organs with the ability to resist stresses. The exploration of the roles of MSCs in overcoming the difactors (17) or by combined differentiation and paracrine effects (37).…”
Section: Constitutive Activation Of P38 Mapk Mediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the secretion of IL-6 by the constitutive activation of the p38 MAPK pathway in MSCs under wound healing; however, discrepancies existed in exploring the underlying mechanisms. MSCs were found serum depletion or hypoxic conditions may act as one of the endogenous responses to various stresses, endowing to mediate the effects by differentiating into skin (25), vessel (12), or neural cells (16), by secreting paracrine tissues or organs with the ability to resist stresses. The exploration of the roles of MSCs in overcoming the difactors (17) or by combined differentiation and paracrine effects (37).…”
Section: Constitutive Activation Of P38 Mapk Mediatesmentioning
confidence: 99%
“…The therapeutic effects were partly attributed to the multilineage potential of MSCs (12,16, the crucial factors contributing to nonhealing wounds (11). Bone marrow-derived stromal or mesenchymal 25,37). We have previously demonstrated that angiogenic factors secreted by MSCs promoted angiogenesis stem cells (MSCs) are capable of self-renewal and have by activating the PI3K-AKT pathway in endothelial of Adult Stem Cells prepared as described previously (35).…”
Section: Introductionmentioning
confidence: 99%
“…Bone-marrow mesenchymal stem cells (BM-MSC) are capable of selfrenewing and of differentiating into various tissues and cells, such as liver epithelium, lung, gastrointestinal tract, and skin cells [204,205]. In fact it was shown that allogeneic BMMSCs significantly enhanced wound healing in normal and diabetic mice through differentiation and release of proangiogenic factors [206].…”
Section: Cell-based Therapiesmentioning
confidence: 99%
“…The MSCs have been shown to possess a strong ability to improve tissue damage in response to skin injury, by contributing to collagen deposition (60), wound contraction (61), angiogenesis (62), regeneration of skin appendages, and enhanced growth of epidermal cells (63). Currently, most of the studies related to MSCs in clinical treatments are on BMMSCs; only limited studies mentioned the application of WJMSCs.…”
Section: Wharton's Jelly Multipotent Stem Cells and Skin Reconstructionmentioning
confidence: 99%